1994
DOI: 10.1111/j.1600-0560.1994.tb00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of cytokeratin and vimentin intermediate filaments in benign and malignant sweat gland tumors

Abstract: The coexpression of cytokeratin and vimentin intermediate filaments has been immunohistochemically evaluated in 124 benign and malignant sweat gland tumors of various types in comparison to normal sweat glands. In addition, all neoplasms have been stained by an antibody to alpha-smooth muscle actin. Epithelial cells reacted with the pan-cytokeratin antibody lu-5. In normal sweat glands, vimentin immunoreactivity was restricted to myoepithelial cells and to some cells of the coiled duct. In benign sweat gland t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
2
15
0
1
Order By: Relevance
“…It has been often difficult to identify vimentin immunostaining in MECs [18,24,33,37], probably due to its restricted distribution in the cytoplasm [19,23]. Despite this difficulty, the present and the previous [6,24,25] studies observed distinct vimentin staining in MECs.…”
Section: Discussionmentioning
confidence: 79%
“…It has been often difficult to identify vimentin immunostaining in MECs [18,24,33,37], probably due to its restricted distribution in the cytoplasm [19,23]. Despite this difficulty, the present and the previous [6,24,25] studies observed distinct vimentin staining in MECs.…”
Section: Discussionmentioning
confidence: 79%
“…3,4 Myoepithelial cells, although commonly encountered in classical spiradenoma and spiradenocylindroma, are not evident at the light microscopic level, but they are convincingly demonstrated by electron microscopy and immunohistochemistry. [5][6][7][8][9] Further morphologic variations include squamous, mucinous, and clear cell differentiation. Malignant transformation results in distinctive appearances including patterns resembling basal cell adenocarcinoma of the salivary gland, either low grade or high grade, infiltrating adenocarcinoma, or sarcomatoid (metaplastic) carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…These have been convincingly demonstrated by electron microscopy and immunohistochemistry. [9][10][11][12][13] Immunohistochemically, these cells have an incomplete myoepithelial cell phenotype. They are often p63 positive but usually lack simultaneous expression of S-100 protein or alpha-smooth muscle actin.…”
Section: Introductionmentioning
confidence: 99%